Kompetenz‐Compétence: What the World Thinks about Arbitrability. Issue 8 (3rd September 2019) - Samuel, Adam
Abstract : The modern pace of legal practice and the gradual assimilation of arbitration into litigation has led to many losses. One of the most notable concerns diminished levels of knowledge about the past.